Analisis Pengaruh Purchase Intention Terhadap Brand Lokal Fashion di Indonesia - Lady, Lady; Dyfan, Dyfan (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
The research was conducted to analyze the influence of the intention to buy on the local fashion brand. The data was collected through purposive sampling and dissemination of questionnaires to the Indonesian public by successfully collecting 374 respondents. This analysis uses SPSS and Smart PLS to test the data. The results of this analysis show that quality of service, brand image, trust, customer relationship, and purchase intention as dependent variables have significant positive influence, while customer satisfaction and perception have no influence. This research is one of the few that uses perception as a mediation variable.